2019
DOI: 10.1557/mre.2020.2
|View full text |Cite
|
Sign up to set email alerts
|

High-voltage applications of the triboelectric nanogenerator—Opportunities brought by the unique energy technology

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 167 publications
(156 reference statements)
0
14
0
Order By: Relevance
“…First, the output voltage of TENGs could reach hundreds to thousands of volts for high-voltage power applications; second, TENGs can effectively reduce the potential issues associated with the unexpected current leakage in traditional high-voltage sources, since the output current of TENGs is usually at the microampere level; Besides, compared with the traditional bulky high voltage source, the light, thin and portable TENG high voltage sources are easier to integrate into the wearable or flexible systems for a wide range of emerging applications. [227][228][229][230]246 For example, Nie et al 230 demonstrated a self-driven microfluidic transport system based on electrowetting technique and an FS-TENG ( Figure 7E). The Coulomb electrostatic field could drive a mini-vehicle consisting of four droplets wheels and a loaded pallet from the FS-TENG's sliding motions ($3500 V).…”
Section: Micro/high-voltage Power Sourcesmentioning
confidence: 99%
“…First, the output voltage of TENGs could reach hundreds to thousands of volts for high-voltage power applications; second, TENGs can effectively reduce the potential issues associated with the unexpected current leakage in traditional high-voltage sources, since the output current of TENGs is usually at the microampere level; Besides, compared with the traditional bulky high voltage source, the light, thin and portable TENG high voltage sources are easier to integrate into the wearable or flexible systems for a wide range of emerging applications. [227][228][229][230]246 For example, Nie et al 230 demonstrated a self-driven microfluidic transport system based on electrowetting technique and an FS-TENG ( Figure 7E). The Coulomb electrostatic field could drive a mini-vehicle consisting of four droplets wheels and a loaded pallet from the FS-TENG's sliding motions ($3500 V).…”
Section: Micro/high-voltage Power Sourcesmentioning
confidence: 99%
“…To obtain the PDMS-NC-porous lms, Sylgard 184 silicone curing agent (0.1 g) was added to the emulsions and stirred for 20 min. Then, the HIPEs were deposited between two glass plates with an area of 4.00 AE 0.07 cm 2 , and cured at 65 C for 24 h. Aer HIPEs curing, the internal phase and the surfactant were removed by washing with water for 48 h and then with ethanol for 24 h. Finally, the polyHIPEs lms were dried at 65 C until constant weight was reached, and were labelled as polyHIPE@X where X was the amount of the colloidal Ag-Nps. In addition, at PDMS-NC lms (without porosity) were prepared by mixing Sylgard 184 silicone elastomer base (1 g) and curing agent (0.1 g) in a 10 : 1 mass ratio, respectively, with different amount of colloidal Ag-Nps (0, 4, 20, 28 and 36 wt% with respect to the total weight of the emulsion) and labelled as F-PDMS@X were X was the amount of the colloidal Ag-Nps.…”
Section: Preparation Of Pdms Lmsmentioning
confidence: 99%
“…Triboelectric nanogenerators (TENGs) have attracted a lot of attention due to their relatively high efficiencies, and large output power, as well as ease of manufacture, low materials costs, and great versatility of possible applications. [1][2][3][4][5] Since the emergence of TENGs, multiple proposals have been made for the improvement of these systems. On the one hand, optimization strategies have focused on device design and there is currently a wide variety of geometries and congurations, [5][6][7][8][9][10][11] while other proposals have focused on the modication of tribomaterials to enhance the energy conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Triboelectric technology has been positively exploited in many fields since Wang’s group first invented triboelectric nanogenerators (TENG), such as self-powered sensors, mechanical energy or blue energy harvesting, and high-voltage occasions [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Apparently, the employment of self-powered sensors in HMI systems can effectively reduce energy requirements since they generate electrical signals directly compared to previous resistive or capacitive sensors [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%